Informing Clinical Research and Practice: Evidence for Environmental Consideration in Neurodegenerative Diseases Policy and Prevention - El-Sherbiny, Menna (AUC Knowledge Fountain, 2025)
Research and practice in the arena of neurodegenerative disease (ND) is fraught with challenges. While the majority of ND are recognized as being idiopathic, or sporadic, most of the attention has focused on risk genes, yet no single gene can account for development of a given ND. Reports recognize “environment” as being a contributing factor, yet environmental considerations are ignored in design of clinical research of diagnostics, or in clinical practice. Review of the literature has identified some of these challenges, which include (1) The disregard for integrating environmental factors, despite the acknowledged preponderance of evidence; (2) The characterization of control (reference groups), as well as those with overt ND in clinical research, thus a perceived missed opportunity towards identifying etiological contributions and prediction; (3) The need to develop non-technical measures and terminology to inform the non-expert clinician, the public and policymakers and the translation of biomedical and environmental innovation towards implementation science (IS). Here, a scoring system for novel autoantibodies against nervous system proteins (i.e., neuroantibodies or NAb) are utilized on archived data in three studies. Study 1, exclusively on asymptomatic reference data, where the scoring system strongly associated with the raw data, differentiated between male and female and rural and urban stratifications, and associated significantly with known neurotoxic metals. Study 2 utilized data from asymptomatic individuals and those diagnosed with Parkinson’s disease (PD) demonstrated that he scoring system proved to have both a great degree of sensitivity and specificity, differentiating between reference and PD subjects, and produced differential profiles for sex, environment, resident governorate and association with heavy metals implicated in PD, namely Cd, Cu and Mn. They also proved to strongly correlate with clinical outcomes. Results in Study 1 and 2 stimulated Study 3 in an attempt to explain differential profiles between governorates, anthropogenic activity, and occupation. The socioeconomic, demographics and industrial-activity that may contribute to environmental degradation and public vulnerability to environmental disease, while challenging, are explored. Finally, recommendation to lay the groundwork towards IS through education of health professionals by reforming curricula, raise awareness among the public, particularly the marginalized, first by tackling illiteracy, and work towards health and environmental literacy in the general public. The need for transparency in data collection, establishing evidence-based policies and enforceable regulations to inform community design, and safeguard the vulnerable with an eye towards environmental justice and knowledgeable stewardship are recommended.